Técnicas activas para mejorar la comprensión lectora, de los estudiantes del sexto año de educación básica de la Escuela Fiscal Mixta El Cosmopolita del cantón Montalvo, provincia de Los Ríos, periodo lectivo 2010- 2011 - Espín Gillacres, Mirian Elizabeth (2012)
Dear reader allows to make a brief summary of our investigation work, the same one that this identified ones with the following topic: "ACTIVE TECHNIQUES to IMPROVE THE UNDERSTANDING READER, OF THE STUDENTS OF THE SIXTH YEAR OF BASIC EDUCATION OF THE SCHOOL "FISCAL MIXED THE COSMOPOLITAN" OF THE CANTON MONTALVO, COUNTY OF THE RIVERS, DURING THE PERIOD LECTIVO 2010 - 2011, to which we have considered him a deserved justification that he/she says this way: The man to put name to all that surrounds it invents certain sounds representing them these with hieroglyphic signs that gave origin to the letter and for ende to the understanding reader, which began to form: phonemes, syllables, words, sentences and sentences; and with all this they structured the texts and the understanding of the written science. The active techniques are instruments that you/they help to the understanding reader and it also considers them to him as a non alone art of more importance for the students but for all the people alphabets, since by means of her he/she obtains a direct information of what happens to our surroundings or, in turn, it is good to go into in the world of the culture, therefore he/she should be practiced it in conscious form to be able to read in an average way and this way to be able to understand the writer's message in all their extension I attach it and to give a legal base of what we will act, we think about the following problem: THE LACK ACTIVE TECHNIQUES doesn't ALLOW THE UNDERSTANDING READER IN THE ACADEMIC YIELD OF THE STUDENTS OF SIXTH YEAR OF BASIC EDUCATION OF THE SCHOOL "FISCAL MIXED THE COSMOPOLITAN, OF THE CANTON MONTALVO, COUNTY OF THE RIVERS, DURING THE PERIOD LECTIVO 2010 - 2011, and to strengthen the investigation work we reinforce with the justification that is characterized to make allusion, to the importance that has this work, the necessity, it is but its beneficiaries, the originality. The active techniques and the understanding reader was centered in the human being and it guarantees its holistic development, in the mark of the respect to the human rights, being important for the knowledge, the exercise of the rights and construction of a sovereign country, constituting in a strategic axis for the national development. The objectives the general and specific they go cooperating to the investigation, likewise we have thought about their objectives that make alucian to the topic: GENERAL OBJECTIVE DTERMINAR THAT THE ACTIVE TECHNIQUES ALLOW THE DEVELOPMENT OF THE UNDERSTANDING READER IN THE ACADEMIC YIELD OF THE STUDENTS OF SIXTH YEAR OF BASIC EDUCATION OF THE SCHOOL "FISCAL MIXED THE COSMOPOLITAN, OF THE CANTON MONTALVO, COUNTY OF THE RIVERS, DURING THE PERIOD LECTIVO 2010 - 2011 SPECIFIC OBJECTIVES. To identify because the educational ones don't apply Active Techniques to secure the understanding reader in the students To diagnose the type of Active Techniques should use to help to the understanding reader, of the sixth year-old students To elaborate a didactic guide on active techniques to improve the understanding reader. For we think about it the following hypothesis: IF we APPLY THE TECHNIQUES ACTIVE IMPROVEMENT CORRECTLY THE UNDERSTANDING READER OF THE STUDENTS OF THE SIXTH YEAR OF BASIC EDUCATION OF THE SCHOOL "FISCAL MIXED THE COSMOPOLITAN" OF THE CANTON MONTALVO, COUNTY OF THE RIVERS, PERIOD LECTIVO 2010 - 2011. "With their variables INDEPENDENT Active techniques. CLERK. Understanding Reader. Next we have the The chapter I it contains the theoretical mark; Here the whole theory related with the investigation topic is developed, considering the variables of the hypothesis, to be able to determine the causes and effects of the problem and power to carry out the investigation to the educational ones and students; with the purpose of looking for alternative of solution to the problem. The chapter II are integrated by the methodological theory; in the one that you/they are detailed: the investigation type, the methods, the techniques to be used in the realization of the work, as well as the population and sample. The chapter III correspond to the analysis of the results obtained in the investigation; here they are presented the statistic in a square and their graphic representation in pastries, to proceed to analyze each one of the questions. What allows to carry out the confirmation of the hypothesis, conclusions and recommendations. The chapter IV refer to the proposal, in her he/she thinks about the title, the introduction, the objectives that love each other to achieve with the proposal, as well as the same development with the positions that are made; and finally the evidence and results of the application of the proposal that it is reflected in the annexes, giving had finished our investigative work.